Molecular diagnosis of mitochondrial respiratory chain disorders in Japan: Focusing on mitochondrial DNA depletion syndrome. Issue 2 (6th March 2014) - Yamazaki, Taro; Murayama, Kei; Compton, Alison G; Sugiana, Canny; Harashima, Hiroko; Amemiya, Shin; Ajima, Masami; Tsuruoka, Tomoko; Fujinami, Ayako; Kawachi, Emi; Kurashige, Yoshiko; Matsushita, Kenshi; et al.
Abstract Background Although mitochondrial respiratory chain disorders (MRCD) are one of the most common congenital metabolic diseases, there is no cumulative data on enzymatic diagnosis and clinical manifestation for MRCD in Japan and Asia. Methods We evaluated 675 Japanese patients having profound lactic acidemia, or patients having symptoms or signs of multiple‐organ origin simultaneously without lactic acidemia on respiratory chain enzyme activity assay and blue native polyacrylamide gel electrophoresis. Quantitative polymerase chain reaction was used to diagnose mitochondrial DNA depletion syndrome (MTDPS). Mutation analysis of several genes responsible for MTDPS was also performed. Results A total of 232 patients were diagnosed with a probable or definite MRCD. MRCD are common, afflicting one in every several thousand people in Japan. More than one in 10 of the patients diagnosed lacked lactic acidemia. A subsequent analysis of the causative genes of MTDPS identified novel mutations in six of the patients. A 335 bp deletion in deoxyguanosine kinase (DGUOK; g.11692_12026del335 (p.A48fsX90)) was noted in two unrelated families, and may therefore be a common mutation in Japanese people. The proportion of all patients with MTDPS, and particularly those with recessive DNA polymerase γ (POLG) mutations, appears to be lower in Japan than in other studies. This is most likely due to the relatively high prevalence of ancient European POLG mutations in Caucasian populations. No other significant differences were identified in a comparison of the enzymatic diagnoses, disease classifications or prognoses in Japanese and Caucasian patients with MRCD. Conclusion MTDPS and other MRCD are common, but serious, diseases that occur across all races.